Wybrane metody taksonomiczne w doborze spółek do portfela - analiza ryzyka - Depta, Adam (Chosen methods in portfolio companies selection - risk analysis, 2006)
In this paper an attempt to evaluation of the risk of portfolios constructed on the basis of selected taxonomic methods was taken. The methods include: taxonomic measure of investments attractiveness (TMAI), generalized distance measure (GDM) as well as relative measure of development. Subsequently, the risk of constructed portfolios was compared with risk level of the single-factor Sharpe model and the Markowitz model.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 299-307